Some psychosocial factors related to the propensity of young adult progenies of subsistence fisherfolks to engage in subsistence fishing in Miagao, Iloilo Feliz Noemi Grace B Espinosa and Chi R. Velasco. - Espinosa, Feliz Noemi Grace B.
The present study sought to demonstrate the relationships between the propensity to engage in subsistence fishing and some psychosocial variables including attitudes towards subsistence fishing, motivations to do subsistence fishing, degree of identification with the subsistence fisherfolk, and the family-rooted normative pressures to continue to do subsistence fishing among progenies of subsistence fisherfolk in Miagao, Iloilo. Respondents were 37 (male=27, female=10), progenies of subsistence fisherfolk with ages ranging from 20 to 25 years. The design of the study was descriptive-correlational. Data were gathered using a questionnaire in a one-on-one setting. Data were analyzed using Spearman's Rho correlational statistic. Results showed significant correlations between the propensity to engage in subsistence fishing and variables motivations to engage in subsistence fishing (rs =0385) and degree of social identification with subsistence fisherfolk (rs =0.349). These support the hypotheses that the higher the motivations in subsistence fishing and the degree of identification as subsistence fisherfolk, the higher the propensity of the young adult progenies of subsistence fisherfolk to engage in subsistence fishing, and vice versa. However, the expected relationships between attitudes toward subsistence fishing and family-rooted normative pressures vis-à-vis were not supported (rs =-.02; p<.05 and rs =0.16; p<.05, respectively). Significant results were explained using some social psychological theories. Cognitive Consistency Theory asserts that human motivation for change is driven by discrepancies and the stress brought on by this out-of-balance inspires people to change their cognitive inconsistencies. Also, the Social Identity Theory (SIT) posits that an individual's identification as part of a certain group influences their tendency to think and behave in the way that the majority of the group does. More research may be done to better understand the social-psychological factors that have implications for engagement in subsistence fishing. Keywords: subsistence fishing, young adults, propensity, attitudes, motivations, social identification, family-based normative pressures.